ANALISIS KINERJA KEUANGAN DAERAH BERBASIS RASIO PADA PEMERINTAH KABUPATEN DAN KOTA SUMATERA UTARA ( STUDI KASUS MEBIDANGROKAT) - Oktarini Khamilah Siregar; Fitri Yani Panggabean (Jurnal Akuntansi Bisnis dan Publik, 2020)
Local governments are very important to evaluate the budget realization report, with the aim of being able to measure the financial performance of the local government each period, so that the Government is encouraged to improve its performance the following year. The government of Regency and city in North Sumatra in the case of Mebidangrokat showed that the ratio of regional financial independence is very significant in increasing the ratio of regional expenditure to PDRB. Local governments should be able to conduct regional financial management planning with the 3E program, as each region has a different geographical, cultural and culture form so that the government's goal in regional financial management is on target.